The History of The Islamic Development In Spain - Azman, Zainal; Supriadi, Supriadi; Helandri, Joni (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
When Islam entered Spain, this country experienced rapid civilization both in terms of Islamic culture and education, because Spain was supported by a fertile country with high enough economic income which produced great thinkers. Spain experienced rapid development and Islamic culture and education began by studying religion and literature, then increasing by studying the sciences of reason. The history of the glory of Islam in Spain needs to be learned from the beginning of its emergence. Therefore, this study explores the history of the arrival of Islam in Spain. This research is qualitative research that describes all data found through a library approach. A bibliographic approach collects literature and previous documents related to the research object. This research does not determine a location as a research location because the study tends to be on text texts. At this stage, activities are carried out by processing data from documents, which will then be compiled into research. The analysis results are presented in the form of a descriptive research report. The results of the study show that the origins of the arrival of Islam in Spain cannot be separated from the success of Tariq ibn Ziyad in defeating King Roderick so this victory became the principal capital for Tariq ibn Ziyad and his troops to conquer essential cities in Spain.